Genotyping of Vitamin-D Receptor (VDR) gene polymorphisms rs7975232, rs1544410, rs731236 and analysis of their association with susceptibility to SARS-CoV-2 among the Kazakh ethnic group - Protas, V.V.; Pogossyan, G.P.; Zhumina, A.G.; Bisseneva, А.К. (Karagandy University of the name of academician E.A. Buketov, 2025)
This pilot study investigated the single nucleotide polymorphisms rs731236, rs1544410, and rs7975232 of the VDR gene using real-time ARMS-PCR in a cohort of 119 individuals of Kazakh ethnic group. Participants were stratified into COVID-19-positive (p-COVID-19; n = 88) and COVID-19-negative (no-COVID-19; n = 31) groups based on the detection of SARS-CoV-2-specific IgM and IgG antibodies by ELISA. The allelic and genotypic distributions of all three SNPs conformed to Hardy–Weinberg equilibrium. No statistically significant differences in allele or genotype frequencies were observed between the groups for rs731236, rs7975232, or rs1544410 (p > 0.05), indicating that these polymorphisms do not influence susceptibility to SARS-CoV-2 infection in the studied population. A borderline association was noted for the heterozygous CT genotype of rs1544410 (p = 0.0548), suggesting a potential protective effect (OR = 0.426; 95 % Cl: 0.1816 — 0.9563). Despite the limited sample size, this is the first study to examine rs731236, rs1544410, and rs7975232 in relation to SARS-CoV-2 susceptibility within the Kazakh ethnic population, as well as one of the few to simultaneously analyze all four alleles of rs1544410.
Keywords: Kazakh ethnic group; susceptibility; COVID-19; SARS-CoV-2; rs1544410; rs7975232; rs731236; single nucleotide polymorphism; vitamin D receptor (VDR) gene; gen; vitamin D; receptor